Anaerobic Propane Oxidation for Biological Sulphateand Thiosulphate Reductions - Gusti Diansyah (Maspari Journal : Marine Science Research, 2014)
The  existence  of  microbial  populations  that  use  short  chain  alkanes  (SCA)  (ethane,  propane  and butane) as potential electron donors for the reduction of sulphate has been recently reported. The useof sulphur compounds in many chemical processing leads wastewaters containing high concentration of  sulphate  and  thiosulphate.  Batch  experiments  were  studied  to  determine  the  ability  of  mixed sediment  cultures  from  Aarhus  and  Eckernförde  Bay  to  anaerobically  reduce  sulphate  and thiosulphate coupled to propane as electron donor.  In the presence of propane, sulphide production from  all  sulphate  and  thiosulphate  bottles  was  higher  than  the  sulphide  production  when  the propane was not added.